1953
DOI: 10.1021/j150508a015
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Colloidal Gold

Abstract: An electron microscope study has been made of the process of reduction of gold chloride to colloidal gold. A method was found of producing gold of uniform size in the diameter range of 200-1500 A. It was found that the particle size distribution curve of colloidal gold preparations is not an error curve but is determined by the kinetics of the process: the nucleation stage and the growth stage. A theory of nucleation is proposed based on the formation of auric ion-organic reducing agent complex which on attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
280
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(291 citation statements)
references
References 0 publications
3
280
2
6
Order By: Relevance
“…All other chemicals were purchased from Sigma-Aldrich (St. Louis, MO) and used as received. Gold nanoparticles (colloid) were synthesized using the Turkevich method [16]; briefly, 1 mL of 29.7 mM HAuCl 4 was added to 100 mL of Milli-Q water (Millipore, 18 MΩ) and brought to a boil, then 1.5 mL of 34 mM sodium citrate was added, and the solution continued to boil for 10 min. Particles were characterized using visible ultraviolet (UV-Vis) spectroscopy (JASCO, V-530), dynamic light scattering (DLS, Malvern Zetasizer Nano-S), and TEM (JEOL 3010 microscope operating at 300 kV).…”
Section: Methodsmentioning
confidence: 99%
“…All other chemicals were purchased from Sigma-Aldrich (St. Louis, MO) and used as received. Gold nanoparticles (colloid) were synthesized using the Turkevich method [16]; briefly, 1 mL of 29.7 mM HAuCl 4 was added to 100 mL of Milli-Q water (Millipore, 18 MΩ) and brought to a boil, then 1.5 mL of 34 mM sodium citrate was added, and the solution continued to boil for 10 min. Particles were characterized using visible ultraviolet (UV-Vis) spectroscopy (JASCO, V-530), dynamic light scattering (DLS, Malvern Zetasizer Nano-S), and TEM (JEOL 3010 microscope operating at 300 kV).…”
Section: Methodsmentioning
confidence: 99%
“…Turkevich et al (1951Turkevich et al ( , 1953 suggested that in citrate reduction, the dicarboxyacetone (DCA) formed from trisodium citrate by thermal decomposition or reduction reaction acts as an organizer to assemble gold ions in a form of multi-molecular complex. The increasing local concentration of precursor facilitates the reduction of Au(III) (Turkevich et al, 1953). The nucleation rate is reportedly enhanced if another stronger organizer (which plays a similar role to DCA) is used.…”
Section: Synthesis Of Ultrasmall Size Gold Nanoparticlesmentioning
confidence: 99%
“…In general, a higher citrate concentration yields a smaller particle size. 39,40 This procedure was first proposed by Hauser and Lynn in 1940 38 and realized some years later by Turkevich et al 41 With slight modifications, it is still in use. Nowadays, commercial suppliers (e.g.…”
Section: Bargheermentioning
confidence: 99%